The effect of unemployment benefits on re-employment rates: Evidence from the Finnish UI-benefit reform - Roope Uusitalo; Jouko Verho (Institute for Labour Market Policy Evaluation (IFAU), 2007)
In January 2003, the unemployment benefits in Finland were increased for workers with long employment histories. The average benefit increase was 15 per cent for the first 150 days of the unemployment spell. In this paper we evaluate the effect of the benefit increase on the duration of unemployment by comparing the changes in the re-employment hazard profiles among the unemployed who became eligible for the increased benefits to the changes in a comparison group whose benefit structure remained unchanged. We find that the benefit increase reduced the re-employment hazards at the beginning of the unemployment spell. The effect disappears after the eligibility period for the increased benefit expires.
Keywords: J64; J65; 330; Unemployment insurance; duration models; Arbeitslosenversicherung; Berufliche Integration; Wirkungsanalyse; Finnland